COVID-19 vs. terrorism: Contribution of the COR theory to the process of coping with invisible threats. (March 2022) - Shelef, Leah; Schiff, Miriam; Pat-Horenczyk, Ruth; Dekel, Rachel
Abstract: Two years have passed since the outbreak of the COVID-19 pandemic. The entire world is still struggling with the virus and its mutations, and governments have been imposing various restrictions, including social distancing and quarantine. This paper leans on the Conservation of Resources (COR) theoretical model in comparing the impact of COVID-19 with that of an ongoing threat of terror attacks, allowing us to understand the similarities and differences between them. Such exploration could result in an understanding that may guide devising psycho-social interventions to minimize the negative psychological consequences of a continuous life-threatening situation. By applying the extensive available literature on the aftermath of terrorist attacks to the little-known long-run consequences of the COVID-19 pandemic, this paper comes up with several guidelines such as increasing online social support and enhancing adaptive coping with stress, that are applicable on the individual, community, and societal levels.